A simple and reliable adult uncuffed endotracheal tube for combined forceps and cryoprobe biopsy during bronchoscopy. (15th September 2022) - Tao, Meimei; Wang, Xinxia; Sun, Qian; Li, Hui; Zou, Hang; Zhu, Guangfa
Abstract: Introduction: Combined forceps and cryoprobe biopsy during bronchoscopy are increasingly used. However, the adult standard cuffed endotracheal tube (SCETT) is can be limited by general anaesthesia and neuromuscular blockade. An adult uncuffed endotracheal tube (UCETT) might provide simple and safe airway support in stable patients during forceps and cryoprobe biopsy under spontaneous respiration. Methods: A retrospective review of stable patients undergoing forceps and cryoprobe biopsy was performed. They were divided into a UCETT group ( N = 33) and a SCETT group ( N = 27). The primary technical outcome was the successful intubation and completion of bronchoscopy. The primary safety outcome was the incidence of desaturation events. Recovery time and side effects were also recorded. Results: UCETTs and SCETTs were successfully inserted, and bronchoscopic procedures were completed in all patients. Only 3/33 (9.1%) patients in the UCETT group exhibited a drop of SPO2 < 90% during the bronchoscopy, compared to 2/27 (7.4%) patients in the SCETT group ( P = 0.545). Patients recovered faster in the UCETT group than those in the SCETT group. Major bleeding, laryngospasm and major arrhythmias did not occur in either group. Incidences of sinus tachycardia, incidences of vomiting, minor and moderate bleeding and premature atrial contractions were not significantly different between the two groups. Nausea occurred in 5/33 (15.2%) patients in the UCETT group, compared to 11/27 (40.7%) in the SCETT group. Conclusion: This study suggests that UCETT under spontaneous respiration can provide satisfactory airway support and a shorter recovery time in stable patients; thus, it may be an option to assist forceps and cryoprobe biopsy. Abstract : An adult uncuffed endotracheal tube (UCETT) group ( N = 33) and a standard cuffed endotracheal tube (SCETT) group ( N = 27) were compared in stable patients undergoing forceps and cryoprobe biopsy during bronchoscopy. The results suggest that UCETT under spontaneous respiration can provide satisfactory airway support and a shorter recovery time in stable patients.